2017
DOI: 10.1096/fj.201700114rrr
|View full text |Cite
|
Sign up to set email alerts
|

Protease‐activated receptor 2 activates airway apical membrane chloride permeability and increases ciliary beating

Abstract: Mucociliary clearance, driven by the engine of ciliary beating, is the primary physical airway defense against inhaled pathogens and irritants. A better understanding of the regulation of ciliary beating and mucociliary transport is necessary for identifying new receptor targets to stimulate improved clearance in airway diseases, such as cystic fibrosis and chronic rhinosinusitis. In this study, we examined the protease-activated receptor (PAR)-2, a GPCR previously shown to regulate airway cell cytokine and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 59 publications
3
45
0
Order By: Relevance
“…Isolation of primary serous acinar cells, immunofluorescence, and live cell imaging of acinar cell volume, pHi (SNARF-5F), and Cl -(SPQ) was carried out as described (10-12, 47, 48). ASL height and pH measurements and ELISAs were carried out as previously reported (92,129,(151)(152)(153)(154)(155)(156)(157). Bacterial growth assays were carried out as previously described (158,159).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation of primary serous acinar cells, immunofluorescence, and live cell imaging of acinar cell volume, pHi (SNARF-5F), and Cl -(SPQ) was carried out as described (10-12, 47, 48). ASL height and pH measurements and ELISAs were carried out as previously reported (92,129,(151)(152)(153)(154)(155)(156)(157). Bacterial growth assays were carried out as previously described (158,159).…”
Section: Methodsmentioning
confidence: 99%
“…We hypothesized that Gi-coupled NPY receptors might blunt the magnitude of VIP-evoked cAMP increases, thus reducing Cland HCO3efflux through CFTR. We measured cellular Clpermeability using 6-methoxy-N-(3-sulfopropyl)quinolinium (SPQ), a dye quenched by Clbut not by NO3 - (48,92). Substitution of extracellular Clfor NO3results in electroneutral influx of NO3and efflux of Cl -, causing a decrease in intracellular [Cl -] ([Cl -]i) and increase in intracellular SPQ fluorescence.…”
Section: Npy Reduces Cftr-mediated Serous Cell Fluid and Hco3secretiomentioning
confidence: 99%
“…A red calcium indicator was used to reduce effects of autofluorescence of the fungal media during acute addition. We and others previously showed that PAR-2 is linked to calcium in airway epithelial cells (8). It is important to note that arrestin binding and G-protein signaling are not mutually exclusive, and our goal was not to quantify the relative contributions of these two pathways (e.g., agonist biasing) in this study.…”
Section: Aspergillus Fumigatus Conditioned Media Can Directly Activatmentioning
confidence: 98%
“…Unless indicated, all reagents and solutions were as described [7,8,67,68]. Full details of materials, reagents, and solution compositions are in the Supplementary Material.…”
Section: Reagents and Solutionsmentioning
confidence: 99%
“…Bitter agonists used and known cognate T2Rs are in Supplementary Table 1. Immunofluorescence (IF) microscopy was carried out as described [7,8,67,68], with more details in the Supplementary Material.…”
Section: Reagents and Solutionsmentioning
confidence: 99%